Equity valuation of Pandora - Pereira, Susana dos Santos (2015)
The purpose of this dissertation was to value Pandora A/S, which is a publicly traded firm on the NASDAQ OMX Copenhagen Stock Exchange in Denmark. Pandora has been increasing its importance in the luxury goods market, more directly in the jewellery segment, due to its remarkable growth and crescent brand awareness. Pandora’s enterprise value was estimated using three different methodologies: discounted cash flows approach, multiples valuation and adjusted present value methodology. The target prices obtained were: 785,76 DKK/share according to the Discounted Cash Flows methodology, 690,77 DKK/share according to Multiples valuation and 779,71 DKK/share if the Adjusted Present Value is used. Since it is believed that the Discounted Cash Flows approach is the most accurate of them, the final estimated target price is 785,76 DKK/share. This result leads to the conclusion that Pandora is undervalued in the stock market, since its actual trading price at May 29 2015 is of 683 DKK/share, representing a potential gain to investors approximately of 103 DKK/share. At last, a comparison between the target price obtained and one estimated by J.P. Morgan was performed. J.P. Morgan presents a target price of 850 DKK/share, higher than the one estimated on this dissertation due mainly to WACC and terminal growth differences.